Advances in Food Allergy Diagnosis - Gomes-Belo, J (2018)
An accurate diagnosis of food allergy is extremely important to guide safe and yet not overly restrictive dietary management. The cornerstone of the diagnosis of food allergy is the clinical history; it allows appropriate selection of the allergens to be tested and interpretation of the results of allergy tests, namely Skin Prick Test (SPT), Specific IgE (sIgE) to allergen extracts and, more recently, specific IgE to allergen components and the Basophil Activation Test (BAT). SPT and sIgE to allergen extracts are very sensitive methods to detect IgE sensitization to a specific food and assess the possibility of spontaneous resolution. Cut-offs have been generated based on the probability of clinical reactivity during oral food challenges and can improve the specificity of SPT and sIgE, helping to confirm the diagnosis of food allergy. Specific IgE to allergen components refines food allergy diagnosis as it allows differentiating species-specific from cross-reactive allergens, aiding the differential diagnosis between a true and potentially severe food allergy from pollen-food syndrome or clinically irrelevant sensitization. The BAT is a new diagnostic test which has high specificity and sensitivity and can complement specific IgE, allowing the deferral of OFC in patients with a positive BAT. Depending on the likelihood of clinical allergy determined based on the combination of the history and the results of allergy tests, an oral food challenge may be indicated to confirm or exclude the diagnosis. Oral food challenge is the gold standard for the diagnosis of food allergy, but is a resource-intensive procedure with some level of risk involved; thus they are reserved for the equivocal cases. This review article discusses the above diagnostic techniques detailing the methods, utility, advantages and disadvantages.